Competitiveness of the Local Corn ‘Manding’ Post the 2022 Fertilizer Subsidy Policy Change - Putri Dwi Utami Nur Hasanah; Elys Fauziyah (Jurnal Ilmu Pertanian Indonesia, 2025)
The agribusiness of food commodities in the Manding District is dominated by local corn. Over 90% of the farmers in the district regularly cultivate Manding variety corn as an alternative crop, planting it at least once a year. The change in the fertilizer subsidy policy in 2022 caused several problems in the district, including a reduction in the availability of fertilizer for farmers due to purchasing quota limitations. This condition leads to unmet fertilizer needs, prompting farmers to purchase non-subsidized fertilizers to cover the shortfall. Consequently, production costs increase significantly. Another issue is the delay in the distribution of subsidized fertilizer, which can affect crop growth and productivity. This situation can impact the competitiveness of corn commodities. This study aims to analyze the impact of government policies on corn commodities and the competitiveness of local Manding corn, considering comparative and competitive advantages. The study area was selected purposively, and 42 corn farmers were chosen as respondents using purposive sampling. Data analysis was conducted using the Policy Analysis Matrix. Based on the analysis, it was found that the government's fertilizer policy could help save costs. Meanwhile, the pricing policy resulted in farmers receiving lower prices than before. Overall, Manding local corn farming in Manding District maintains both competitive and comparative advantages. This is evidenced by the Private Cost Ratio and the Domestic Resource Cost Ratio, both of which have values less than one. Keywords: competitiveness, corn, government policy, Manding corn